The Effect of Parental Phubbing on Depression in Chinese Junior High School Students: The Mediating Roles of Basic Psychological Needs Satisfaction and Self-Esteem - Xiao, Xiaofang; Zheng, Xifu (Frontiers in Psychology, 2022)
Objective:To reveal the relationship between the parental phubbing, basic psychological needs, self-esteem and depression as well as the mechanism of how parental phubbing impacts on depression. Methods : A total of 1038 junior high school students were investigated using the parental phubbing scale, basic psychological needs scale, self-esteem scale and depression scale in combination. Results:(1)Parental phubbing was significantly correlated with their basic psychological needs, self-esteem and depression.(2)Parental phubbing can not only be used to directly predict depression in junior middle school students, but also have an indirect impact on depression through three pathways: a separate mediating effect of basic psychological needs, a separate mediating effect of self-esteem and a chain mediating effect of both. Conclusion: Parental phubbing is a risk factor of depression, which can affect the mental health of junior high school students negatively.